“Lashing Out at ‘Intellectuals’”: Facing Fear on Both Sides of the Desk - Stephanie Paterson (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
The author identifies stages in working through a personal attack in a student's composition. Turning toward conflict in a teacher researcher stance is a creative, self-renewing way to conduct the ongoing (often unexplored) intellectual-emotional work of writing teachers.